LITERASI DIGITAL: KUNCI MENUJU PENDIDIKAN BERKUALITAS MELALUI PERSPEKTIF SDGS 2030 - Tasliah, Ade Lia; Nuraeni, Adila; Rachman, Ichsan Fauzi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Education is a key foundation in a country's development. However, the challenges of accessibility and quality of education are still a global problem. Digital literacy is an effective solution in overcoming these obstacles. Digital literacy enables individuals to access, understand, evaluate and use information critically, creatively and responsibly in the digital world. This is crucial to achieving quality education, which is one of the main goals of the 2030 Sustainable Development Goals (SDGs). Quality education should be inclusive, equitable and of high quality, while promoting lifelong learning opportunities for all. Digital literacy plays an important role in achieving these goals by providing access to a wider range of information and educational resources, enabling students to learn independently, and encouraging collaboration and communication on a global scale. By utilizing digital technology, education can become more affordable, efficient and environmentally friendly. This is part of the effort to improve access to education for all, including the underprivileged and marginalized. This article will discuss the definition of digital literacy, its benefits for education and the challenges of its implementation. In addition, this article will also provide some recommendations to improve digital literacy in Indonesia. As such, this article highlights the importance of digital literacy in transforming education towards better quality and achieving sustainable development goals. Through collaborative efforts between the government, educational institutions and the community, digital literacy can be the main key in opening up opportunities for equitable and quality education for all, and supporting the realization of the 2030 SDGs.).